Initial treatment for surgery-naïve desmoid tumors by high intensity focused ultrasound - Shen, Jiayi; Zhao, Jing; Zhong, Xian; Xie, Shuyi; Wu, Lanqi; Hu, Chenlu; Hu, Xiaoye; Shen, Hong (Frontiers in Oncology, 2024)
Desmoid tumor (DT) is a rare proliferative disease occurring in connective tissues, characterized by high infiltration and recurrence rates. While surgery remains the primary treatment, its recurrence risk is high, and some extra-abdominal desmoid tumors are inoperable due to their locations. Despite attempts with radiotherapy and systemic therapy, the efficacy remains limited. Here, we explored low-power cumulative high-intensity focused ultrasound (HIFU) therapy as an initial treatment for desmoid tumor patients either ineligible or unwilling for surgery. Low-power cumulative HIFU employs slower heat accumulation and diffusion, minimizing damage to surrounding tissues while enhancing efficacy. Fifty-seven non-FAP desmoid tumor patients, previously untreated surgically, underwent low-power cumulative HIFU therapy. Among them, 35 had abdominal wall DT, 20 had extra-abdominal DT, and 2 had intra-abdominal DT, with an 85% median ablation ratio. Abdominal wall DT patients showed significantly better response rates (91.4% vs. 86%) and disease control rates (100% vs. 32%) than that of non-abdominal wall DT patients. Median event-free survival time was not reached after a median follow-up duration of 34 months. With its high response rate, durable efficacy, and mild adverse effects, our findings suggest that low-power cumulative HIFU presents a promising novel treatment for desmoid tumors, particularly abdominal wall DT patients.